Pengujian Sistem Informasi Lembaga Donasi Berbasis Web Menggunakan Metode Black Box Testing dan Teknik Equivalence Partitions - Subhana; Prasetyo Hadi Wibowo; Rikardus Wuli Dike; Azhari Hidayat; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Testing is needed on the application to find out whether the application is a bug or needs to be improved to make it better. The black-box testing method has been widely used by researchers to test application suitability. The application being tested is a contribution system application consisting of menus that the administrator wants to enter. When the testing process produces bugs that were previously unknown, then the test is considered a good test. The purpose of application testing is to see if the program performs every function we expect without looking at the source code of the software's functions. The type of black-box testing procedure used in this study is equivalence partitioning. The equivalence division process is a test that starts with filling in each form on each input menu, the content to be tested starts with valid or invalid.